1997
DOI: 10.1074/jbc.272.37.23201
|View full text |Cite
|
Sign up to set email alerts
|

SUG1, a Component of the 26 S Proteasome, Is an ATPase Stimulated by Specific RNAs

Abstract: RNA, but not by poly(A)؊ RNA. RNA transcribed in vitro from cDNA encoding a b-Zip protein could stimulate the ATPase activity. This is the first report to demonstrate a specific RNA requirement for ATPase with respect to the proteasomal ATPases. Our present work suggests that SUG1 can specifically interact with protein-coding RNA (mRNA) and play some roles in mRNA metabolism.The 26 S proteasome is a huge protease complex that degrades short-lived proteins related to metabolic regulation and cell cycle progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Yeast and mouse SUG1s have been reported to bind to its cognate TBP. In a previous work, we determined that rat SUG1 was 44 kDa in molecular mass (Makino et al 1997). Taken together, we conclude that TIP43 contains SUG1.…”
Section: Identification Of Sug1 In Tips Separated By Two-dimensional supporting
confidence: 67%
See 1 more Smart Citation
“…Yeast and mouse SUG1s have been reported to bind to its cognate TBP. In a previous work, we determined that rat SUG1 was 44 kDa in molecular mass (Makino et al 1997). Taken together, we conclude that TIP43 contains SUG1.…”
Section: Identification Of Sug1 In Tips Separated By Two-dimensional supporting
confidence: 67%
“…HIV Tat has been found to stimulate transcription elongation mediated by a cellular factor (Zhou & Sharp 1995), and MSS1 and TBP1 are thought to regulate HIV gene expression via Tat. We demonstrated that rat SUG1 ATPase was stimulated by specific RNAs (Makino et al 1997). Recently, Russell et al (1999) reported that the yeast SUG1 and SUG2 are involved in nucleotide-excision repair.…”
Section: Are Proteasomal Atpases Candidates For Transcriptional Regulmentioning
confidence: 78%
“…4 for simplicity) likely targets the receptor for ubiquitination and subsequent proteolysis by the 26S proteasome complex. (185)(186)(187) The availability of a cell-free transcription system in which VDR-RXR heterodimers activate transcription in a 1,25(OH) 2 D 3 -dependent fashion (188) should facilitate studies of transcriptional control by VDR, such as demonstrating direct effects by coactivators, promoter-specific factors, or corepressors. Ultimately, with such cell-free transcription systems it may also be feasible to incorporate elements of chromatin structure such as the aforementioned histones, in order to develop a system that truly mimics VDR action in vivo while at the same time permitting manipulations, in vitro.…”
Section: Vitamin D Receptormentioning
confidence: 99%
“…It has been suggested that the ubiquitin-proteasome pathway plays an important regulatory role in nuclear receptor function, adding a new dimension to the field of nuclear hormone receptors (10,32,33,39). Besides ubiquitin-protein ligases, such as E6-AP; RSP5 (reverses Spt phenotypes) and its human homologue, RPF-1 (receptor potentiation factor 1) (23,39); UBA3, a ubiquitin-activating enzyme of the NEDD8 pathway (12,16); the GAL4 suppressor SUG1 (suppressor of Gal4D lesions 1) (14,33); and UBC9 (46), the human homologue of Saccharomyces cerevisiae E2 ubiquitin-conjugating enzyme of the sumoylation pathway, are some of the components of the ubiquitin-proteasome pathway and ubiquitin-like pathways that have been shown to modulate the properties of steroid receptors.…”
mentioning
confidence: 99%